1992
DOI: 10.1902/jop.1992.63.8.696
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Pyrophosphate and Sodium Dodecyl Sulfate on Periodontal Pathogens

Abstract: Our previous studies have shown that pyrophosphate (PPi), the anticalculus component of tartar‐control dentifrices, inhibits the growth of organisms associated with coronal and root surface caries. The purposes of this investigation were to: 1) determine if periodontal pathogens are similarly susceptible to the growth‐inhibitory properties of PPi; and 2) determine if combinations of pyrophosphate‐sodium dodecyl sulfate (PPiSDS) inhibit growth synergistically. Porphyromonas gingivalis, Actinobacillus actinomyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…j) in comparison to those treated with PBS 1×, SDS has also been shown to kill planktonic Aggregatibacter actinomycetemcomitans cells at a minimum inhibitory concentration (MIC) of 0·1 g l − 1 (Drake et al . ; Wade and Addy ). As SDS causes protein unfolding at concentrations above its critical micelle concentration (Otzen ), these findings suggest that SDS mediated biofilm detachment results from the denaturation of proteinaceous matrix adhesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…j) in comparison to those treated with PBS 1×, SDS has also been shown to kill planktonic Aggregatibacter actinomycetemcomitans cells at a minimum inhibitory concentration (MIC) of 0·1 g l − 1 (Drake et al . ; Wade and Addy ). As SDS causes protein unfolding at concentrations above its critical micelle concentration (Otzen ), these findings suggest that SDS mediated biofilm detachment results from the denaturation of proteinaceous matrix adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…The anionic surfactant SDS, a common ingredient in dental cleaning agents, exhibits bactericidal activity against numerous oral bacteria (Drake et al 1992;Wade and Addy 1992). SDS is thought to kill bacteria by penetrating the cytoplasmic membrane and causing cell lysis (Adair et al 1979).…”
Section: Discussionmentioning
confidence: 99%
“…These Gram‐negative bacteria initiate a host response mediated by cytokines that results in destruction of connective tissue and alveolar bone loss. Successful management of chronic inflammatory periodontal disease can be achieved by a combination of mechanical and chemotherapeutic agents 3 . In addition, it has been shown that removal of bacterial plaque or suppression of the total microbiota reduces the severity of chronic inflammatory periodontal disease 4 …”
mentioning
confidence: 99%
“…Successful management of chronic inflammatory periodontal disease can be achieved by a combination of mechanical and chemotherapeutic agents. 3 In addition, it has been shown that removal of bacterial plaque or suppression of the total microbiota reduces the severity of chronic inflammatory periodontal disease. 4 Proinflammatory cytokines such as interleukin (IL) -1 and tumor necrosis factor-alpha (TNF -a) have been implicated in the pathogenesis of tissue destruction in periodontitis.…”
mentioning
confidence: 99%
“…Pyrophosphate and diphosphonates not only affect mineralization processes in plaque but have been shown also to inhibit growth of oral bacteria, including those of both supragingival and subgingival plaque (6,7). Pyrophosphate can inhibit formation of in vitro plaque (19), and may act as an antiplaque agent, especially in conjunction with other agents active against oral bacteria.…”
mentioning
confidence: 99%